Faktor Fundamental Kinerja Keuangan Terhadap Harga Saham Lq45 - Rachma Zannati; Endang Budiarti (Oikonomia: Jurnal Manajemen, 2021)
Purpose Aims to find out the implications of the Fundamental Factors of Financial Performance (Earning Per Share, Dividend Per Share, Return On Assets, BI Rate Interest Rate and Inflation) on stock prices in LQ45 companies.  Methodology The period used in this study is 5 (five) years with the existing sample criteria obtained 23 companies. The analysis technique used is panel data regression. Findings The results of data analysis show that Earning Per Share, Dividend Per Share, Return On Assets, and Inflation have no significant effect on stock prices, while only the BI Rate has significant implications for stock prices. Suggestion Develop other variables to obtain generalizable results and expand the research sample. The limitations of the research are only using subjects in the LQ45 sector and the variation of variables is only limited to fundamental factors.